An Oceanic Tale: Trauma, Technology and Cultural Resistance in Richard Powers’s Playground - Bezrukov , Andrii; Bohovyk , Oksana (American & British Studies Annual, 2025)
The article appears to be one of the first academic treatments of Richard Powers’s Playground (2024) to delve into the intertwining narratives of humanity and nature within the Anthropocene epoch. Powers examines the ethical, emotional, and existential dilemmas posed by climate change and technological advancement through his characters and their engagement with an aquatic ecosystem. We explore how the author addresses the issues of environmental (ocean) pollution, AI, childhood trauma, (de)humanisation, and cultural resistance to reflect the complexities of the human condition represented in Anthropocene fiction. Within the interdisciplinary realm, we bring together various perspectives from the (environmental) humanities and ecocultural studies, emphasizing the crucial significance of discussing current crises through culture. An ecocritical reading of Playground reveals how Powers critiques anthropocentrism and illustrates the consequences of ecological neglect, ultimately advocating for a more harmonious coexistence with the natural world. Powers’s captivating story of personal tragedies, environmental issues, anxieties of the Anthropocene, cultural myths, and the critique of overreliance on technology prompts readers to reflect on their roles within the global ecosystem, the importance of environmental stewardship, and the urgency of addressing climate change, while fostering a sustainable future.